2021
DOI: 10.1101/2021.04.23.441209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insertions in SARS-CoV-2 genome caused by template switch and duplications give rise to new variants that merit monitoring

Abstract: The appearance of multiple new SARS-CoV-2 variants during the winter of 2020-2021 is a matter of grave concern. Some of these new variants, such as B.1.351 and B.1.1.17, manifest higher infectivity and virulence than the earlier SARS-CoV-2 variants, with potential dramatic effects on the course of the COVID-19 pandemic. So far, analysis of new SARS-CoV-2 variants focused primarily on point nucleotide substitutions and short deletions that are readily identifiable by comparison to consensus genome sequences. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…This FCS has not yet been found in other sarbecoviruses, but it is present in other Beta-CoV subgenera [4,5,90,91]. One hypothesis about the origin of the FCS is that it was generated naturally by a template switch, followed by substitutions that eventually erased its similarity to the original sequence [87]. The FCS sequences of several CoVs resemble polybasic low-complexity regions that tend to evolve fast [92].…”
Section: Evolution By Insertions/deletionsmentioning
confidence: 96%
See 1 more Smart Citation
“…This FCS has not yet been found in other sarbecoviruses, but it is present in other Beta-CoV subgenera [4,5,90,91]. One hypothesis about the origin of the FCS is that it was generated naturally by a template switch, followed by substitutions that eventually erased its similarity to the original sequence [87]. The FCS sequences of several CoVs resemble polybasic low-complexity regions that tend to evolve fast [92].…”
Section: Evolution By Insertions/deletionsmentioning
confidence: 96%
“…Large-scale SARS-CoV-2 sequencing data (>1.7 million genomes) coupled with sophisticated bioinformatics analyses have revealed many such events, which are located more frequently at the 3 half of the genome. These occur especially at the spike region and have the potential to lead to escape from neutralizing antibodies or even T-cell immunity [87]. For example, the Omicron variant has three deletions and one insertion within the spike and three deletions in other genomic regions.…”
Section: Evolution By Insertions/deletionsmentioning
confidence: 99%
“…This scenario seems plausible, since it has been shown that insertions are not infrequent in SARS-CoV-2 and that "although this insert has a high GC-content compared to the genomic average of SARS-CoV-2, it falls within the GC-content range of the long inserts'' and is located within 20 nucleotides of a template switch hotspot at position 22 582. [33] Furthermore, Holmes et al reported that "both CGG codons are more than 99.8% conserved among the > 1,800,000 near complete SARS-CoV-2 genomes sequenced to date," [10] suggesting that these codons are preserved by stabilizing selection and, therefore, may be associated with high fitness. In this regard, the FCS insertion structure appears to be well consistent with the hypothesis of natural origin and subsequent evolution-driven codon optimization.…”
Section: Points Of Disagreement With the Segreto / Deigin Hypothesismentioning
confidence: 99%
“…This scenario seems plausible, since it has been shown that insertions are not infrequent in SARS‐CoV‐2 and that “although this insert has a high GC‐content compared to the genomic average of SARS‐CoV‐2, it falls within the GC‐content range of the long inserts'' and is located within 20 nucleotides of a template switch hotspot at position 22 582. [ 33 ]…”
Section: Points Of Disagreement With the Segreto / Deigin Hypothesismentioning
confidence: 99%
See 1 more Smart Citation